Dinéjí Na`nitin : Navajo Traditional Teachings and History - McPherson, Robert S., 1947- (Book collections on Project MUSE., 2012)
"Traditional teachings derived from stories and practices passed through generations lie at the core of a well-balanced Navajo life. These teachings are based on a very different perspective on the physical and spiritual world than that found in general American culture. Dinejí Na'nitin is an introduction to traditional Navajo teachings and history for a non-Navajo audience, providing a glimpse into this unfamiliar world and illuminating the power and experience of the Navajo worldview. Historian Robert McPherson discusses basic Navajo concepts such as divination, good and evil, prophecy, and metaphorical thought, as well as these topics' relevance in daily life, making these far-ranging ideas accessible to the contemporary reader. He also considers the toll of cultural loss on modern Navajo culture as many traditional values and institutions are confronted by those of dominant society. Using both historical and modern examples, he shows how cultural change has shifted established views and practices and illustrates the challenge younger generations face in maintaining the beliefs and customs their parents and grandparents have shared over generations. This intimate look at Navajo values and customs will appeal not only to students and scholars of Native American studies, ethnic studies, and anthropology but to any reader interested in Navajo culture or changing traditional lifeways."--Project Muse.